Adaptive vibration control on electrohydraulic shaking table system with an expanded frequency range: Theory analysis and experimental study. (1st October 2019) - Liu, Jinxin; Qiao, Baijie; Zhang, Xingwu; Yan, Ruqiang; Chen, Xuefeng
Highlights: Electrohydraulic shaking table (EHST) system includes servo and target controller. The effective frequency bandwidth is extended by new designed servo controller. An adaptive power level control algorithm is proposed for target control. Experiment was conducted on a 3-ton EHST system with a 1.2 m × 1.2 m table. The results show the system can finally match the target within an accuracy of ±3 dB. Abstract: Active vibration control using electrohydraulic shaking table (EHST) system is widely applied in civil engineering, automotive industry, environmental vibration testing and other situations where large actuating forces are needed. However, the electrohydraulic actuators (actuating systems) often suffer from drawbacks of limited frequency bandwidth, varying system parameters and so forth. In view of the limits mentioned above, this study hopes to seek out proper solutions to minimize the influence from those drawbacks. We first design a full state feedback-feedforward servo controller, which is able to extend the frequency bandwidth of EHST system, by constructing the analytical models of the servo valve and hydraulic cylinder. Numerical simulations show that the proposed servo controller is able to compensate for the attenuation-band of hydraulic cylinder and thus improve the upper frequency limit of the whole system to a degree that is higher than the natural frequency of servo valve. Afterwards, we propose a frequency domain adaptive power level control (APLC) algorithm for solving the problem of parametric variations of EHST system in application of power level control (i.e., simulate vibration based on certain power spectrum). Numerical simulations show that although APLC algorithm is not able to get exactly same spectrum and waveform at every independent trial, the power level of every trail will finally converge to the target power spectrum. Finally, an experimental validation was conducted based on an EHST system with 3 ton maximum force and 1.2 m × 1.2 m horizontal table. The results show that the proposed algorithms have greatly improved the effective bandwidth and the power level of the controlled system response can finally match the target power spectrum within an accuracy of ±3 dB.